ANALISIS PENGARUH FAKTOR-FAKTOR QUALITY OF WORK LIFE TERHADAP WORK ENGAGEMENT PADA KARYAWAN SWASTA GENERASI Z DI KOTA KUPANG - Rohani Purnamasari Dima; Heni M Sauw; Natalya Marzella Pandy (ITB AAS Indonesia Surakarta, 2024)
This research is motivated by the issue of Generation Z, which constitutes the largest population in Indonesia, and many of them have entered the workforce. This generation has a low attachment to their jobs, making them prone to changing jobs easily. Quality of Work Life is an independent variable that is crucial for companies to meet the physical and psychological needs of their employees, and Work Engagement, as the dependent variable, is how individuals survive and engage with their jobs. This research focuses on Generation Z who have worked as private employees in Kupang City. This study aims to determine the effect of Quality of Work Life on Work Engagement in Generation Z. Based on hypothesis testing using the Multiple Linear Regression analysis method, with the assistance of SPSS 27 for Windows analysis tools, the results obtained showed the influence of Quality of Work Life factors on Work Engagement of 0.83%. Furthermore, the significance level of the regression test showed a significance value of 0.000 <the Significance Criterion (0.05), indicating that the regression model meets the linearity criteria. Keywords: Quality of Work Life, Work Engagement, Generation Z, Kupang City